Estructura de propiedad de las firmas y grupos económicos: el caso chileno - Paredes M., Ricardo (1993)
It analyzes the ownership structure of Chilean firms and the effect that conglomerates or economic groups produce on this structure. The central hypothesis is that the ownership structure of firms owned or controlled by economic groups is not significantly different from the ownership structure of any other firm. The variables analyzed were ownership structure, optimal size of the firm, potential control, regulation, economic group and tradability of the good or productive sector. The most relevant finding is the evidence that the ownership structure of the firms belonging to economic groups is significantly different (more concentrated) from that of the rest of the firms in the sample, which would indicate that the firms belonging to groups do not maximize benefits individually, but as a whole.